2022
DOI: 10.1159/000525056
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of the TEMPI Syndrome with Pomalidomide Plus Dexamethasone Followed by Autologous Stem Cell Transplantation

Abstract: TEMPI syndrome is a rare disease associated with plasma cell neoplasms. Although previous studies have reported that bortezomib is effective as a 1st-line treatment for TEMPI syndrome, some cases are refractory to this treatment. Pomalidomide, a kind of immunomodulatory drugs, is widely used for the treatment of relapsed or refractory multiple myeloma and could be administered without dose modification in patients with renal dysfunction. We present a case of bortezomib-refractory TEMPI syndrome with renal insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Patients with TEMPI syndrome generally have a dramatic response to plasma cell‐directed treatment which has included bortezomib, lenalidomide, and daratumumab [5–9]. As with our case, some authors have reported that treatment with ASCT has yielded long‐term responses [10].…”
Section: Figuresupporting
confidence: 61%
“…Patients with TEMPI syndrome generally have a dramatic response to plasma cell‐directed treatment which has included bortezomib, lenalidomide, and daratumumab [5–9]. As with our case, some authors have reported that treatment with ASCT has yielded long‐term responses [10].…”
Section: Figuresupporting
confidence: 61%
“…Bone marrow biopsy typically shows findings consistent with those of MGUS or smoldering myeloma [ 92 ]. Initial treatment with daratumumab or bortezomib is recommended, but other drugs and autologous stem cell transplants are also effective [ 93 , 94 , 95 , 96 , 97 ]. The increase of serum erythropoietin or the M-protein, as well as the reemergence of telangiectasias, may be used as markers of relapse.…”
Section: Mgcs As a Global And Unifying Conceptmentioning
confidence: 99%